2022
DOI: 10.3389/fphar.2022.899164
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Capture-Recapture Method to Estimate the Frequency of Community- and Hospital-Acquired Drug-Induced Acute Kidney Injuries in French Databases

Abstract: Drug-induced acute kidney injury (AKI) can occur both in primary care (i.e., community-acquired AKI (CA-AKI)) and in hospital settings (i.e., hospital-acquired AKI (HA-AKI)). The reported prevalence of these events varies markedly from one study to another, mainly due to differences in the study design. To estimate the frequency of drug-induced AKIs (both CA-AKIs and HA-AKIs) observed in a French university hospital, we applied the capture-recapture method to 1) the French national pharmacovigilance database (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In addition, community- and hospital-acquired DI-AKI differ in several ways. A retrospective study in France showed that antibiotics, diuretics, and contrast agents were significantly more associated with cases of hospital-acquired DI-AKI, while antineoplastics, lipid-lowering drugs, hypoglycemic agents, and immunosuppressive agents were mostly associated with cases of community-acquired DI-AKI ( Rey et al, 2022 ). Besides the common drugs mentioned, the nephrotoxicity of some botanical drugs should also be considered, though all of them do not drive DI-AKI ( Su et al, 2011 ; Yang et al, 2018 ).…”
Section: Research Status Of Di-akimentioning
confidence: 99%
“…In addition, community- and hospital-acquired DI-AKI differ in several ways. A retrospective study in France showed that antibiotics, diuretics, and contrast agents were significantly more associated with cases of hospital-acquired DI-AKI, while antineoplastics, lipid-lowering drugs, hypoglycemic agents, and immunosuppressive agents were mostly associated with cases of community-acquired DI-AKI ( Rey et al, 2022 ). Besides the common drugs mentioned, the nephrotoxicity of some botanical drugs should also be considered, though all of them do not drive DI-AKI ( Su et al, 2011 ; Yang et al, 2018 ).…”
Section: Research Status Of Di-akimentioning
confidence: 99%